National Identity: Transformation Trends - Lyubov I. Sedova (Гуманитарный вектор)
The significance of this study is determined by the permanent, multidirectional social and cultural transformations both at the global and local levels that occur in the information society. These changes are caused by globalization, development of information and telecommunication technologies, intensification of cultural exchange and extension of mass culture. The purpose of this paper is to identify the most important transformation trends of the national identity. The originality of the results is presented by: (1) the definition of the main trends of national identification process in information society; (2) the study of the specialty of Russian identity. The theoretical and methodological basis of the article is formed by the wide range of domestic and foreign theories. These theories are dedicated to the problems of information society and social identity. We use analytical and comparative methods at the stage of formulation the problem and substantiating the theoretical foundations of the study. We also worked out the questionnaire, which was used during data collection. In the part of the project dedicated to the discussing the results and making conclusions, the method of systematization and synthesis was used. These methods allow us to identify some transformation trends of national identity in the information society. In particular, the crisis of national (state) identity, the spread of particularism and the coexistence of many competing local identities, an appeal to the basic culture values in search of the foundations of a national community were distinguished. The practical significance of the study is determined by the value of the results for the specialists in social philosophy, philosophy of history, social psychology and related disciplines.